Calcidiol (25-hyroxy vitamin d3) -a healer of Cardiovascular disease - MEENATCHI SUNDARAM ANGAPPAN; DR. KARUPIAH JEYAPRAKASH (International Journal of Pharma and Bio Sciences, 2017)
Calcidiol also known as 25-hydroxy vitamin D3 is a steroid prohormone synthesised in the liver. 25-hydroxy vitamin D3 is major form of vitamin D in the circulation and the major storage form in the liver. In the renal tubules and in variety of tissues such as endothelial cells, vascular smooth muscle cells, and bone, the 25-hydroxy vitamin D3 is further hydroxylated by 1-alpha-hydroxylase. The product is 1-alpha, 25 -dihydroxy vitamin D3 or calcitriol, the most potent vitamin D metabolite. Several epidemiologic and clinical studies have suggested that low levels of vitamin D affect the cardiovascular system. Lower plasma vitamin D levels are correlated with a higher risk of incident hypertension. Prolonged vitamin D deficiency causes secondary hyperparathyroidism. An increased PTH is associated with myocardial contractility which leads to cardiac hypertrophy and calcification of heart valves. This article reviews the role of vitamin D in cardiovascular health; however, the cardioprotective hypothesis of vitamin D to date is inconclusive. This should be explored further whether cardiovascular disease is treatable with supplemental vitamin D.